Magnetic and thermal scaling of electric machines. (6th December 2012) - Pries, Jason; Hofmann, Heath
In this paper, we will investigate performance relationships between electric machines whose dimensions are related by a uniform scaling factor. It is shown, assuming that the voltages applied to the scaled machine windings possess the same magnitude as those applied to the original 'unit' machine, that a corresponding scaling of the time domain ensures the magnetic fields in the machine are consistent with the original, unscaled machine. Furthermore, under the assumption of linear thermal conduction within the machine materials, it is shown that the temperature profile is consistent as well, provided the scaled cooling system can maintain the same temperatures at the machine's boundaries. This serendipitous result allows for straightforward scaling of machine performance characteristics, such as torque-speed curves and efficiency maps, which may be particularly useful for variable-speed and automotive applications.